2018
DOI: 10.1017/s1049023x18001140
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis Prevalence and Comorbidity in a Population of Mobile Integrated Community Health Care Patients

Abstract: IntroductionFrequent calls to 911 and requests for emergency services by individuals place a costly burden on emergency response systems and emergency departments (EDs) in the United States. Many of the calls by these individuals are non-emergent exacerbations of chronic conditions and could be treated more effectively and cost efficiently through another health care service. Mobile integrated community health (MICH) programs present a possible partial solution to the over-utilization of emergency services by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…– Clients with certain risk profiles rostered to programs by primary care providers [ 81 82 92 112 126 ], hospitals [ 51 52 95 108 120 127 ], or by paramedic services [ 55 56 128 ]…”
Section: Resultsmentioning
confidence: 99%
“…– Clients with certain risk profiles rostered to programs by primary care providers [ 81 82 92 112 126 ], hospitals [ 51 52 95 108 120 127 ], or by paramedic services [ 55 56 128 ]…”
Section: Resultsmentioning
confidence: 99%
“…16,17 Some studies suggest that they may have unresolved problems or call frequently because they are not aware of an alternative pathway to access appropriate care. 6,[16][17][18][19][20][21] A 2022 review identified only one qualitative paper-from Canada-reporting experiences of people making frequent emergency ambulance calls. 22 Management of people who make frequent calls to ambulance services is a priority for United Kingdom (UK) ambulance services.…”
Section: Introductionmentioning
confidence: 99%
“…People who make frequent calls are often vulnerable, 6,13–15 more likely to: be from low socioeconomic groups; live alone; experience mental health challenges including self‐harming behaviour; live with chronic conditions; and have increased chances of falling 16,17 . Some studies suggest that they may have unresolved problems or call frequently because they are not aware of an alternative pathway to access appropriate care 6,16–21 . A 2022 review identified only one qualitative paper—from Canada—reporting experiences of people making frequent emergency ambulance calls 22 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation